Video-endoscopic mobilization of the gracilis muscle for rectourinary fistula repair: case report - Britto, Cesar; Pfalzgraf, Daniel Philipp; Lima, Ronnie; Medeiros, Paulo; Rebouças, Rafael; Passerotti, Carlo (Urologia internationalis, 2021)
Introduction: Transposition of the gracilis has been used in a large number of reconstructive procedures. Its advantage is its proximity to these defects and a good blood supply. Traditionally, the gracilis mobilization is performed by open surgery with one or more incisions. We describe our initial experience with the video-endoscopic mobilization of gracilis. Method: We described a retrospective review of all patients who underwent gracilis muscle mobilization for treatment of rectourethral fistula, performed by video-endoscopy, between March 2013 and September 2017, for treatment of rectourethral fistula. Also, our surgical technique is described in detail. Results: Three patients, with a mean age of 66.6 years, underwent the procedures. The mean time for mobilization of the gracilis was 107 min (range 60-145). There was no case of donor area infection, no change in the sensitivity of the medial aspect of the thigh or chronic pain. Conversion to open surgery was not necessary in any case. The hospital discharge occurred in average after 4 days. The bladder catheter was removed after 4 weeks after cystography was performed without evidence of leakage. One patient had a recurrence of the fistula. Discussion: The gracilis is an excellent choice of tissue to be interposed in reconstructive procedures of the perineal region, especially in the treatment of rectourinary fistulas. However, endoscopic harvest of the gracilis muscle has not yet found its way into everyday practice. The results in the treatment of rectourinary fistulas are excellent, with a success rate of 87.7%. Our rate of 67% is below, probably due to the small number of cases. In open surgery, complications are uncommon; however, approximately half of the patients expressed concern about the painful scar, which can be reduced by minimally invasive access. Conclusion: Video-endoscopic mobilization of gracilis muscle for the treatment of rectourethral fistula is feasible and safe. Studies comparing this technique with the conventional mobilization are required.